Coping Humor of Entrepreneurs: Interaction Between Social Culture and Entrepreneurial Experience - Lin, Song; Li, Jing; Han, Rui (Frontiers in Psychology, 2018)
It is feasible to deal with the high pressures in entrepreneurship using humor. This paper studies the effect of interaction between entrepreneurs’ perception of social culture and entrepreneurial experience (including experience with entrepreneurial failure and current company performance) on coping humor of entrepreneurs with a sample of 171 entrepreneurs from Bohai Rim in China. Regression analysis revealed that entrepreneurs would be more likely to adopt coping humor when they perceived supportive social culture to entrepreneurship and had experienced entrepreneurial failure or when they perceived supportive social culture to entrepreneurship and had good current business. This study contributes to the literature of the theory of humor, the culture of entrepreneurship, and entrepreneurial failure.